The Impact of Investment on Economic Growth in Savannakhet Province Between 2009-2024 - VONGKHASEUM, Bounphan; TOUNMANYSONE, Thongsa (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study has two main objectives: (1) to examine the overall investment situation in Savannakhet Province from 2009 to 2024, and (2) to analyze the impact of investment on the province’s economic growth during the same period. The study employs time series data and applies multiple regression analysis using the Ordinary Least Squares (OLS) method, supported by statistical software to estimate coefficients and determine the relationships between dependent and independent variables. The findings reveal that between 2009 and 2024, Savannakhet Province attracted a total of USD 2,510,397,254 in foreign investment. The industrial sector received the largest share, totaling USD 1,702,193,500, with China emerging as the leading investor. Meanwhile, state investment amounted to 3,952.30 billion kip. In 2024, the exchange rate was 21,933 kip per US dollar, and the trade balance recorded USD 6,731.90 million. The OLS estimation results indicate that economic growth is significantly influenced by state investment (PI) and the kip–US dollar exchange rate, at the 90% and 95% confidence levels, respectively. These findings provide valuable insights for policymakers and relevant stakeholders in planning and promoting sustainable economic development in Savannakhet Province.